1998
DOI: 10.1177/1420326x9800700504
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Airborne Bacteria and Fungi in Bayside Offices in Rio de Janeiro, Brazil

Abstract: This paper provides the first published information on indoor concentrations of micro-organisms in a building in Rio de Janeiro, Brazil. The building in question was a 1,000 m2, twenty-nine-story building with a central air conditioning system. Concentrations and genera of bacteria and fungi were determined in several offices using a 6-stage impactor (Andersen sampler) during the summer season. Several gram-positive (Micrococcus, Bacillus, Staphylococcus, Streptococcus) and gram-negative (Pseudomonas, Serratia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In contrast, Brickus et al 25. found that the microbiological concentration in the indoor air was similar to the outdoor values, which means that the I/O concentration ratio was close to 1 25. However, by comparing obtained average values of I/O ratios with that proposed by Neto and Siqueira26 (I/O ≤ 1.5 = good; I/O = 1.5–2.0 = regular; I/O > 2 = poor indoor conditions), the indoor conditions among cases can be considered to be relatively poor when compared to a regular indoor conditions among controls.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, Brickus et al 25. found that the microbiological concentration in the indoor air was similar to the outdoor values, which means that the I/O concentration ratio was close to 1 25. However, by comparing obtained average values of I/O ratios with that proposed by Neto and Siqueira26 (I/O ≤ 1.5 = good; I/O = 1.5–2.0 = regular; I/O > 2 = poor indoor conditions), the indoor conditions among cases can be considered to be relatively poor when compared to a regular indoor conditions among controls.…”
Section: Discussionmentioning
confidence: 89%
“…This is no doubt the consequence of inadequate ventilation increased the number of occupancy. In contrast, Brickus et al 25. found that the microbiological concentration in the indoor air was similar to the outdoor values, which means that the I/O concentration ratio was close to 1 25.…”
Section: Discussionmentioning
confidence: 89%
“…were commonly isolated from university rooms in Poland [51]. Micrococcus , Bacillus and Staphylococcus were isolated in a building in Brazil [67]. The CoNS, Micrococcus and Corynebacterium were found to be the predominant genera in different parts of a hospital and primary schools located in Edirne, Turkey and Staphyloccus species were the most prevalent bacteria in all sampled months [30,68].…”
Section: Resultsmentioning
confidence: 99%
“…mycotoxins) play a major role in SBS. The fungal spores can constitute up to 70% of all bioaerosol pollution of indoor air (Brickus et al, 1998;Reynolds et al, 2001).…”
Section: Introductionmentioning
confidence: 99%